Proceedings of the 5th International Conference on Indonesian Social and Political Enquiries, ICISPE 2020, 9-10 October 2020, S 2021
DOI: 10.4108/eai.9-10-2020.2304765
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice and Social Distance of Diponegoro University Students in Establishing Inter-Personal Relationship with Members from Different Ethnic Groups

Abstract: This study aims to measure the social distance and social prejudice of Diponegoro University students in terms of friendship and marriage based on gender. This study uses the intertwining conceptual perspective between identity and social distance. The research method used is a survey involving 415 students from various ethnic backgrounds, which are Javanese, Chinese, Sundanese, Batak, Minang, and Papuan. This study found that 415 students have low social distance in terms of friendship and marriage. In terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…They concluded that students from different ethnicities did not experience obstacles in interacting or making friendships. Only a few want to avoid marrying women or men of other ethnicities(Turnomo Rahardjo et al, 2021). In Malaysia, most students (60%) feel happy to befriend students from various ethnicities (Agus Masrukhin & H. Sriyanto, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that students from different ethnicities did not experience obstacles in interacting or making friendships. Only a few want to avoid marrying women or men of other ethnicities(Turnomo Rahardjo et al, 2021). In Malaysia, most students (60%) feel happy to befriend students from various ethnicities (Agus Masrukhin & H. Sriyanto, 2022).…”
Section: Discussionmentioning
confidence: 99%